The Effect of Collagen Activation on Platelet Rich Plasma for Proliferation of Periodontal Ligament Fibroblasts - Pati Tangsupati; Kwartarini Murdiastuti (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: Regenerative procedure in periodontal surgery aims to improve the structure and function of the periodontium to be strong enough to support the teeth. Growth factor is essential in the process of tissue regeneration; it can be generated from the activation of Platelet-Rich Plasma (PRP). In this study, collagen was used as PRP activator. PRP release growth factor from the granules when activated. The aim of this study was to evaluate the effect of collagen on PRP activation and the collagen-activated PRP storage to fibroblast proliferation of periodontal ligament (PDL).METHODS: Fibroblasts of PDL were obtained from extracted premolar. PRP were obtained from 100 mL of blood donors using double centrifugation methods. PRP were activated by collagen and subsequently incubated for 24, 48, 72 and 168 hours; after which the lysate was taken. Fibroblasts were divided into 7 groups, which consisted of one unstimulated group as negative control, one group stimulated by PRP lysate, and five groups stimulated with PRP-collagen lysates that had been incubated for 24, 48, 72 and 168 hours. MTT assay was then performed after 1 and 3 days.RESULTS: The proliferation rate of fibroblasts group stimulated by PRP-collagen lysate was higher than the group stimulated by PRP. The storage of collagen-activated PRP for 7 days at 4°C could increase the proliferation rate.CONCLUSION: The activation of collagen on PRP and the stored collaged-activated PRP could increase the fibroblasts proliferation rate of PDL.KEYWORDS: collagen, platelet-rich plasma, fibroblasts proliferation